2017
DOI: 10.3855/jidc.8152
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella spp. and hematological changes in privately owned domestic cats from Rio de Janeiro, Brazil

Abstract: Introduction: Bartonella infection in cats can represent a risk to owners, particularly today when considering the increase in cat populations and their role in human bartonellosis epidemiology. In the present study, we aimed to detect Bartonella spp. in blood samples from 163 asymptomatic privately-owned cats from the metropolitan area of Rio de Janeiro State, Brazil by using a conventional PCR test and also to evaluate the association between Bartonella spp. and hematological changes in positive cats. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…11 On the other hand, researchers demonstrated that hematological findings in Bartonella spp.-infected cats may be uncommon. 44 It is important to note that other clinical conditions may also cause this hematological change, such as infection by intestinal parasites and skin or respiratory abnormalities found in cats from this study. Further studies are needed to establish the correlation between eosinophilia and Bartonella infection.…”
Section: Discussionmentioning
confidence: 81%
“…11 On the other hand, researchers demonstrated that hematological findings in Bartonella spp.-infected cats may be uncommon. 44 It is important to note that other clinical conditions may also cause this hematological change, such as infection by intestinal parasites and skin or respiratory abnormalities found in cats from this study. Further studies are needed to establish the correlation between eosinophilia and Bartonella infection.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanisms of anemia were studied mainly in B. bacilliformis and were described in various ways [ 73 ]. Bartonella -positive animals frequently showed anemia, eosinophilia, neutrophilia, and thrombocytopenia in [ 14 , 74 ]. Additionally, Bartonella -infected cats mostly showed mild or no abnormality of blood panels [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature review demonstrates that bacteremic animals may transmit infection when they have no clinical disease, and this can occur months after their initial inoculation. 23 Indeed, evidence of current or prior infection is common in both domestic and stray animals, 24 and has been reported in up to 75% 25 in certain regions. Even if a pet is not currently infested with fleas, they can potentially still transmit from prior exposures, 26 and possibly via saliva.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, PCR from blood is often sufficient to confirm infection. 25 A sample treatment regimen for a cat would be doxycycline and fluoroquinolone for 4–6 weeks. 1 , 2 , 12 A family experiences serial cases of CSD.…”
Section: Discussionmentioning
confidence: 99%